The Strategic Role of Medical Affairs Department in a Pharmaceutical Company - Słomiak, Krzysztof (Strategiczna rola działu medycznego w firmie farmaceutycznej, 2024)
The pharmaceutical industry is a highly regulated and strategic sector of the national and global economies. Through the years it became one of the most important areas of governmental interest and control because of its impact on the state of society. The Medical Affairs Department in a pharmaceutical company is one of the areas that individuals with medical training or experience are most interested in working in. This department’s extensive operational breadth impacts all aspects of how a pharmaceutical company is run, serving as a guardian over regulatory compliance, business strategy and pharmacovigilance for the available and ongoing medical issues. Understanding the subtleties of the relationships and linkages between Medical Affairs and any other area of such large corporations is not always easy. In this article, I investigated and discussed the strategic role of the Medical Affairs Department in a pharmaceutical company to explore how the competitive advantage for the company is being built with the use of this specific department.
Słomiak, K. (2024). The Strategic Role of Medical Affairs Department in a Pharmaceutical Company. W J. Radomska & A. Witek-Crabb (red.), New Trends in Business Management (s. 47–63). https://doi.org/10.15611/2024.30.7.04
Keywords: medical affairs; medical affairs department; pharmaceutical industry; pharmaceutical company; strategy; dział medyczny; przemysł farmaceutyczny; firma farmaceutyczna; strategia